Mycelium-Based Composite: The Future Sustainable Biomaterial - Alemu, Digafe; Tafesse, Mesfin; Mondal, Ajoy Kanti (International Journal of Biomaterials, 2022)
Because of the alarming rate of human population growth, technological improvement should be needed to save the environment from pollution. The practice of business as usual on material production is not creating a circular economy. The circular economy refers to an economic model whose objective is to produce goods and services sustainably, by limiting the consumption and waste of resources (raw materials, water, and energy). Fungal-based composites are the recently implemented technology that fulfills the concept of the circular economy. It is made with the complex of fungi mycelium and organic substrates by using fungal mycelium as natural adhesive materials. The quality of the composite depends on both types of fungi and substrate. To ensure the physicochemical property of the fabricated composite, mycelium morphology, bimolecular content, density, compressive strength, thermal stability, and hydrophobicity were determined. This composite is proven to be used for different applications such as packaging, architectural designs, walls, and insulation. It also has unique features in terms of low cost, low emission, and recyclable.